2017
DOI: 10.1186/s12963-017-0124-6
|View full text |Cite
|
Sign up to set email alerts
|

Change in life expectancy with type 2 diabetes: a study using claims data from lower Saxony, Germany

Abstract: BackgroundThis study estimates life expectancy with and without type 2 diabetes for individuals in Lower Saxony, Germany in order to detect a trend in population health.MethodsMorbidity and mortality data derived from German administrative claims data (statutory health insurance, AOK Niedersachsen, N = 2,900,065) were used covering 10 years from 2005 to 2014. Life table analysis was applied for calculating life expectancy, life expectancy free of type 2 diabetes, life expectancy with type 2 diabetes, and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…However, our analysis did show a gradual increase in life expectancy and reduction in mortality, particularly for the female diabetic population for the period 2012-2015. Similarly, Muschik et al(2017) concluded that the life expectancy among diabetics in Lower Saxony, Germany had been increasing for the period 2005-2014, but the paper has not made any comparative analysis of diabetic patients with general population [7]. Logically, diabetes-related mortality rates rise as the age of patients progresses, which have been demonstrated in previous studies [4].…”
Section: Plos Onementioning
confidence: 91%
See 1 more Smart Citation
“…However, our analysis did show a gradual increase in life expectancy and reduction in mortality, particularly for the female diabetic population for the period 2012-2015. Similarly, Muschik et al(2017) concluded that the life expectancy among diabetics in Lower Saxony, Germany had been increasing for the period 2005-2014, but the paper has not made any comparative analysis of diabetic patients with general population [7]. Logically, diabetes-related mortality rates rise as the age of patients progresses, which have been demonstrated in previous studies [4].…”
Section: Plos Onementioning
confidence: 91%
“…longer duration of disease). [7] In Bulgaria current prevalence estimates put the number of people diagnosed with diabetes at almost 500 000 people (6.5% of the population), where the highest prevalence is seen between the ages of 60 and 74 [8]. The most recent estimates point that a further 2.5% are with undiagnosed diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…diabetes). A recent German study of healthcare claims data from 2005 to 2014 found that the proportion of life spent with type 2 diabetes increased with life expectancy (188). However, it could not be ascertained if this was an expansion of morbidity or a dynamic equilibrium, due to a lack of disease severity data.…”
Section: Healthy Ageing and Morbidity Evidencementioning
confidence: 99%
“…We are not aware of any existing study that has examined trends in the remaining life expectancy for populations with a history of hip fracture, myocardial infarction, or stroke-even though the latter two conditions are the most common causes of death both in Sweden and globally [21]. A few studies that have explored trends in life expectancy among population subgroups with, for instance, diabetes or some cancer types have reported converging trends, i.e., a narrowing gap between life expectancy in the general population and among subgroups with a history of disease [22,23]. A persistent gap was, however, found for population subgroups with lung cancer [23].…”
Section: Introductionmentioning
confidence: 99%